Long-term outcome of patients with hereditary transthyretin V30M amyloidosis with polyneuropathy after liver transplantation. (2nd January 2016) - Okumura, Kosuke; Yamashita, Taro; Masuda, Teruaki; Misumi, Yohei; Ueda, Akihiko; Ueda, Mitsuharu; Obayashi, Konen; Jono, Hirofumi; Yamashita, Satoshi; Inomata, Yukihiro; Ando, Yukio
Abstract: Background : Liver transplantation halts production of mutated transthyretin (TTR), and thus it is an accepted treatment, with improved survival, in patients with hereditary (familial) amyloidosis with polyneuropathy (FAP). However, the effects of transplantation on the clinical manifestations of FAP have not yet been adequately clarified. This study aimed to investigate whether liver transplantation would improve the long-term clinical manifestations in FAP patients who had undergone transplantations. Patients and methods : We assessed 29 non-transplant and 36 transplant FAP V30M patients using an FAP clinical scoring system. Results : The total clinical score of the non-transplant group increased and was significantly correlated with FAP duration; that of the transplant group increased slowly after transplantation. In patients 5 years or more after FAP onset, the total clinical scores of the transplant group were significantly lower than those of the non-transplant group. In the same patients, scores for sensory, motor, autonomic and organ impairments of the transplant group were significantly lower than those of the non-transplant group. Conclusions : Liver transplantation had beneficial effects on FAP clinical manifestations in patients with FAP TTR V30M. Liver transplantation should therefore be considered as an effective treatment in the clinical management of patients with FAP TTR V30M.